Using PICO Methodology to Answer Questions About Smoking in COPD Patients (2017)
The ALAT and SEPAR Treatment and Control of Smoking Groups have collaborated in the preparation of this document which attempts to answer, by way of PICO methodology, different questions on health interventions for helping COPD patients to stop smoking. The main recommendations are: (i) moderate-quality evidence and strong recommendation for performing spirometry in COPD patients and in smokers with a high risk of developing the disease, as a motivational tool (particularly for showing evidence of lung age), a diagnostic tool, and for active case-finding; (ii) high-quality evidence and strong recommendation for using intensive dedicated behavioral counselling and drug treatment for helping COPD patients to stop smoking; (iii) high-quality evidence and strong recommendation for initiating interventions for helping COPD patients to stop smoking during hospitalization with improvement when the intervention is prolonged after discharge, and (iv) high-quality evidence and strong recommendation for funding treatment of smoking in COPD patients, in view of the impact on health and health economics. © 2017 SEPAR